Ceramic paraffin lubricant for PVC (polyvinyl chloride) plates

By using ceramic paraffin lubricant, paraffin is contained in the pores of ceramic powder, the problem of paraffin migration and precipitation in PVC sheet production is solved, extending the production interval and improving production efficiency and product quality.

CN119119579APending Publication Date: 2024-12-13NANJING TECH UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411320516.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-29
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

During the production process of PVC sheets, the compatibility between paraffin and PVC is poor, resulting in paraffin being easy to migrate and precipitate, affecting production efficiency and product appearance. In addition, after 2-3 days of continuous production under conventional processes, a large amount of paraffin will condense after the mold outlet of the mold, and it is necessary to stop and clean it up. .

Method used

Use ceramic paraffin lubricant to replace paraffin. By mixing paraffin with ceramic powder, the pores of ceramic powder are used to accommodate paraffin. Paraffin melts at high temperature and promotes the movement of ceramic powder, reducing paraffin precipitation and adsorbing in ceramic powder channels during cooling. , avoid paraffin condensation.

Benefits of technology

The production interval was extended, and condensed paraffin appeared at the mold outlet for 26-28 days after continuous production, which significantly reduced the migration and precipitation of paraffin and improved production efficiency and product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119579A_ABST
    Figure CN119119579A_ABST
Patent Text Reader

Abstract

The invention discloses a ceramic paraffin lubricant for a PVC (polyvinyl chloride) plate. The ceramic paraffin lubricant is prepared by the following steps: (1.1) mixing secondary aluminum ash, silicon dioxide, kaolin, montmorillonite and a binder, granulating, drying and roasting to obtain a granular ceramic sintered body; (1.2) crushing and grinding the granular ceramic sintered body to obtain ceramic powder; (1.3) dividing the ceramic powder into two parts, namely first ceramic powder and second ceramic powder; the preparation method comprises the following steps: heating paraffin to a molten state at 60-80 DEG C under a vacuum condition, dipping the first ceramic powder into the molten paraffin to enable the paraffin to permeate into micropores of the ceramic powder, cancelling vacuum, adding the second ceramic powder into the paraffin, and uniformly stirring to form the ceramic paraffin lubricant. According to the ceramic paraffin lubricant, in the cooling process of a PVC plate, pore channels in ceramic powder can form a vacuum state, paraffin near the ceramic powder can be adsorbed into the pore channels of the ceramic powder, and the outward precipitation amount of the paraffin is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application. The application date of the original application is April 29, 2024. The application number is 2024105244364. The name of the invention is: A method for producing PVC sheets with low paraffin precipitation. Technical Field

[0002] The invention relates to a ceramic paraffin lubricant for PVC plates. Background Art

[0003] In the production process of PVC sheets, paraffin needs to be added as an external lubricant to reduce the friction between the processing equipment and the processing process. However, due to the poor compatibility of paraffin with PVC, it is easy to migrate and precipitate from the surface of the PVC sheet during the production and subsequent use of the PVC sheet, affecting the production efficiency and the appearance of the product. In the production process, the released paraffin will condense as the temperature of the PVC sheet decreases, and the condensed paraffin will adhere to the outlet of the shaping mold. At present, after 2-3 consecutive productions, a large amount of paraffin will be generated at the outlet of the shaping mold, affecting the normal production. It is necessary to stop the machine and clean the condensed paraffin before continuing production. Therefore, how to reduce the migration of paraffin and improve the production efficiency and use quality of PCV sheets has become a need. Summary of the invention

[0004] In order to reduce the migration of paraffin in PVC sheets, the present application proposes a production method of PVC sheets with low paraffin precipitation, wherein the production raw material formula includes the following components in parts by weight: 100 parts of PVC resin powder, 2-4 parts of heat stabilizer, 2-4 parts of processing aid, 1-2 parts of ceramic paraffin lubricant, 0.5-1.3 parts of stearic acid, 3-4 parts of toughening agent, 50-65 parts of calcium carbonate, and 40-50 parts of secondary aluminum ash;

[0005] The production method comprises the following steps:

[0006] (1) stirring the components to form a raw material mixture;

[0007] (2) adding the raw material mixture into an extruder for extrusion;

[0008] (3) The extruded melt is cooled to room temperature through a shaping die to obtain a PVC sheet.

[0009] The heat stabilizer is calcium stearate, barium stearate or calcium-zinc composite heat stabilizer, the processing aid is acrylate copolymer, the toughening agent is chlorinated polyethylene, and the calcium carbonate is preferably heavy calcium carbonate.

[0010] In the present application, a ceramic paraffin lubricant is used to replace paraffin as an external lubricant. The ceramic paraffin lubricant is a mixture of ceramic powder and paraffin. Part of the paraffin can enter the pores of the ceramic powder. Since the volume of the paraffin increases by about 10% when the solid state changes to a liquid state, part of the paraffin in the pores of the ceramic powder can be discharged from the ceramic powder to continue to play a lubricating role. In the present application, the volume of the paraffin in the ceramic paraffin lubricant is greater than the volume of the ceramic powder, and most of the paraffin is still in a free state. During the process of passing through the extruder, the paraffin will not be invalidated, and the paraffin can continue to play a role of external lubrication.

[0011] When the raw material mixture passes through the extruder, the air contained in the raw material mixture expands and is discharged due to heat, and the air in the ceramic powder is also discharged due to heat. When the PVC sheet is formed, the outside air can no longer enter the interior of the PVC sheet. During the cooling process of the PVC sheet, the pores in the ceramic powder will form a vacuum state, and the paraffin near the ceramic powder will be adsorbed into the pores of the ceramic powder, reducing the amount of paraffin precipitated outward. At present, when conventional processes are used to produce PVC sheets, a large amount of paraffin will condense at the outlet of the shaping mold after 2-3 days of continuous production, and it is necessary to temporarily stop the production and clean up the condensed paraffin in the shaping mold and other areas. After adopting this application, condensed paraffin will appear at the outlet of the shaping mold after 26-28 days of continuous production.

[0012] Specifically, the ceramic paraffin lubricant is prepared by the following method:

[0013] (1.1) secondary aluminum ash, silicon dioxide, kaolin, montmorillonite and a binder are mixed, granulated, dried and calcined to obtain a granular ceramic sintered body; the binder is at least one of bentonite, tetraethyl orthosilicate and polyvinyl alcohol;

[0014] (1.2) crushing and grinding the granular ceramic sintered body to obtain ceramic powder;

[0015] (1.3) The ceramic powder is divided into two parts, namely a first ceramic powder and a second ceramic powder; under vacuum conditions, paraffin is heated at 60-80°C to a molten state, and the first ceramic powder is immersed in the paraffin melt to allow the paraffin to penetrate into the micropores of the ceramic powder. The vacuum is canceled, and the second ceramic powder is added to the paraffin, and stirred evenly to form a ceramic paraffin lubricant.

[0016] In step (1.2), the granular ceramic is ground using a vertical mill.

[0017] The ceramic powder formed under the above conditions has a large number of pores for accommodating paraffin. The ceramic powder is divided into two parts, one of which is mixed with paraffin under vacuum, and the other is mixed with paraffin under normal pressure. When mixed under vacuum conditions, paraffin can enter the pores of the first ceramic powder and fill the pores. When the first ceramic powder enters the extruder, under the action of high temperature, the paraffin in the pores of the first ceramic powder melts and sprays outward, which can promote the movement of the first ceramic powder and drive the movement of the surrounding second ceramic powder, avoid the agglomeration of the ceramic powder, and improve the uniformity of the ceramic powder in the PVC sheet. The pores of the second ceramic powder contain only a small amount of paraffin. In the process of passing through the extruder, the air in the second ceramic powder expands and is discharged from the pores. In the cooling process of the PVC sheet, the paraffin still in a liquid state can enter the pores of the first ceramic powder and the second ceramic powder, and adsorb the paraffin in the pores to avoid its precipitation.

[0018] Specifically, in step (1.1), the mass ratio of secondary aluminum ash, silica, kaolin, montmorillonite and binder is (70-80):(10-15):(1-5):(3-8):(1-5).

[0019] If the amount of secondary aluminum ash added is too low, the Al2O3 content in the ceramic will be too low, and the porosity in the ceramic powder will be too low, which will affect the penetration of paraffin into the ceramic powder and reduce the adsorption performance of paraffin. When the amount of secondary aluminum ash added is high, the strength of the resulting ceramic powder will be poor.

[0020] Specifically, in step (1.1), the calcination process is as follows: the temperature is first increased to 600-650°C at a heating rate of 8-12°C / min, then increased to 900-1000°C at a heating rate of 3-6°C / min, kept warm for 1-2h, then cooled to room temperature, and then increased to 1300-1350°C at a heating rate of 8-12°C / min, and kept warm for 1-3h.

[0021] After the temperature reaches 600-650℃, AlN and metallic aluminum in the secondary aluminum ash begin to oxidize. Too fast a heating rate can easily cause expansion and cracking of the ceramic body. At a lower heating rate, the full oxidation of AlN and metallic aluminum can be guaranteed. After the oxidation of AlN and metallic aluminum is completed, the structure of the ceramic sintered body is basically formed. After cooling to room temperature, the temperature is raised to 1300-1350℃ again, and during the insulation process, it gradually reaches the ceramic phase, so that the ceramic sintered body can expand rapidly and produce cracks inside, so that it can be split into irregular particles in the subsequent crushing and grinding process, which is conducive to the adsorption of paraffin.

[0022] When the temperature is lower than 1300℃, the strength of the ceramic will be too low, the ceramic body will be easy to break, and it is not conducive to storing more paraffin. When the temperature is higher than 1350℃, excessive casting will occur, reducing the number of pores in the ceramic body. Under the above conditions, the porosity of the formed ceramic powder is 40-52%. The secondary aluminum ash also contains a certain amount of cryolite. During the sintering process of the ceramic, the cryolite and aluminum nitride in the secondary aluminum ash will produce gas, which is more conducive to the formation of porous materials in the ceramic.

[0023] Specifically, in step (1.2), the granular ceramic sintered body is crushed and ground, and then sieved with a 400-500 mesh screen, and the sieved material is taken as ceramic powder. Under the above particle size, while ensuring that the formed ceramic paraffin lubricant can pass through the screw extruder smoothly with other components of the plastic, the ceramic powder can also absorb more paraffin. If the particle size of the ceramic powder is too large, it will cause difficulty in discharging the extruder.

[0024] Furthermore, in order to remove the air in the ceramic powder as much as possible, in step (1.3), the vacuum degree is 20-100Pa absolute pressure.

[0025] Specifically, to ensure the amount of paraffin wax, in step (1.3), the volume ratio of ceramic powder to paraffin wax is 1:(1.5-2.5). Under the above ratio, part of the paraffin wax is absorbed into the ceramic powder, and part of the paraffin wax is wrapped on the surface of the ceramic powder, and can continue to serve as a lubricant.

[0026] Specifically, to avoid excessive paraffin wax adsorption in the ceramic powder, the volume ratio of the first ceramic powder to the second ceramic powder is (20-30): (70-80). When the proportion of the first ceramic powder is too large, although the uniformity of the ceramic powder in the material can be improved, the amount of paraffin wax adsorbed by the ceramic powder will be reduced during the cooling process, which is not conducive to the adsorption and locking of the paraffin wax. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the SEM image of the 1# ceramic powder prepared in Example 1.

[0028] Figure 2 This is another SEM image of the 1# ceramic powder prepared in Example 1.

[0029] Figure 3 This is the EDS spectrum of 1# ceramic powder prepared in Example 1.

[0030] Figure 4 This is the X-ray diffraction pattern of the 1# ceramic powder prepared in Example 1. DETAILED DESCRIPTION

[0031] Example 1

[0032] Preparation of 1# ceramic paraffin lubricant:

[0033] (1.1) The secondary aluminum ash, silicon dioxide, kaolin, montmorillonite and binder are mixed with a high-speed mixer, granulated, dried and calcined to obtain a granular ceramic sintered body; the binder is specifically bentonite. The mass ratio of secondary aluminum ash, silicon dioxide, kaolin, montmorillonite and binder is 75:12:3:6:4. The drying temperature is 120°C, the drying time is 3h, and the calcination process is as follows:

[0034] The temperature was first increased to 620°C at a rate of 10°C / min, then slowly increased to 950°C at a rate of 4°C / min, kept at this temperature for 1.5 h, then cooled to room temperature, and then increased to 1320°C at a rate of 10°C / min, and kept at this temperature for 2.5 h.

[0035] (1.2) The granular ceramic sintered body is crushed and ground by a vertical mill and sieved by a 400-mesh screen, and the sieved material is taken as 1# ceramic powder. The porosity of 1# ceramic powder is 48%. The SEM image obtained when testing the ceramic powder in this embodiment is as follows: Figure 1 and Figure 2 The obtained EDS spectrum is shown in Figure 3 The obtained X-ray diffraction pattern is shown in Figure 4 shown.

[0036] (1.3) Divide the 1# ceramic powder into two parts, namely the first ceramic powder and the second ceramic powder, and the volume ratio of the first ceramic powder to the second ceramic powder is 20:80. Under the vacuum condition of 50Pa absolute pressure, heat the paraffin at 75°C to a molten state, immerse the first ceramic powder in the paraffin melt, and allow the paraffin to penetrate into the micropores of the first ceramic powder. After the vacuum is canceled, add the second ceramic powder into the paraffin, stir evenly, and form the 1# ceramic paraffin lubricant. The volume ratio of 1# ceramic powder to paraffin is 1:2.

[0037] The production of PVC sheets, the production raw material formula includes the following components by weight:

[0038] 100 parts of PVC resin powder, 4 parts of heat stabilizer, 3 parts of processing aid, 1.5 parts of 1# ceramic paraffin lubricant, 1 part of stearic acid, 3 parts of toughening agent, 55 parts of heavy calcium carbonate, 40 parts of secondary aluminum ash; the heat stabilizer is specifically a calcium-zinc composite heat stabilizer, the processing aid is specifically an acrylate copolymer, the toughening agent is specifically chlorinated polyethylene, and the mesh number of the secondary aluminum ash is 500-600 mesh.

[0039] The production method comprises the following steps:

[0040] (1) stirring the components to form a raw material mixture;

[0041] (2) The raw material mixture is added into a twin-screw extruder for extrusion. The temperature of each zone of the twin-screw extruder is: Ⅰ (conveying section) 195°C, Ⅱ (melting section) 185°C, Ⅲ (metering section) 175°C, Ⅳ (die head) 180°C.

[0042] (3) The extruded melt is pressed and formed by a calender, and then peeled and cooled to room temperature to obtain a PVC sheet.

[0043] In this embodiment, the chemical composition (dry basis) of the secondary aluminum ash is as follows (mass percentage):

[0044] Element <![CDATA[Al2O3]]> MgO <![CDATA[SiO2]]> <![CDATA[Fe2O3]]> Cl <![CDATA[Na2O]]> CaO F AlN other content 58.87 2.73 10.46 2.74 2.45 2.23 2.19 2.16 12.13 4.04

[0045] Example 2

[0046] Preparation of 2# ceramic paraffin lubricant:

[0047] (1.1) The secondary aluminum ash, silicon dioxide, kaolin, montmorillonite and binder are mixed with a high-speed mixer, granulated, dried and calcined to obtain a granular ceramic sintered body; the binder is specifically bentonite. The mass ratio of secondary aluminum ash, silicon dioxide, kaolin, montmorillonite and binder is 80:11:2:4:3. The drying temperature is 120°C, the drying time is 3h, and the calcination process is as follows:

[0048] The temperature was first increased to 600°C at a rate of 9°C / min, then slowly increased to 910°C at a rate of 3°C / min, kept at this temperature for 1.8 hours, then cooled to room temperature, and then increased to 1350°C at a rate of 8°C / min, and kept at this temperature for 1.5 hours.

[0049] (1.2) The granular ceramic sintered body is crushed and ground by a vertical mill and sieved by a 500-mesh screen, and the sieved material is taken as 2# ceramic powder. The porosity of 2# ceramic powder is 42%.

[0050] (1.3) The 2# ceramic powder is divided into two parts, namely the first ceramic powder and the second ceramic powder, and the volume ratio of the first ceramic powder to the second ceramic powder is 25:75. Under the vacuum condition of 80Pa absolute pressure, the paraffin is heated at 73°C to a molten state, and the first ceramic powder is immersed in the paraffin melt to make the paraffin penetrate into the micropores of the first ceramic powder. The vacuum is canceled, and the second ceramic powder is added to the paraffin, and stirred evenly to form a 2# ceramic paraffin lubricant. The volume ratio of the 2# ceramic powder to the paraffin is 1:2.5.

[0051] For the production of PVC sheets, the raw material formula includes the following components in parts by weight: 100 parts of PVC resin powder, 2 parts of heat stabilizer, 2 parts of processing aid, 1 part of 2# ceramic paraffin lubricant, 0.8 parts of stearic acid, 3.5 parts of toughening agent, 50 parts of heavy calcium carbonate, and 50 parts of secondary aluminum ash; the heat stabilizer is specifically barium stearate, the processing aid is specifically acrylic acid ester copolymer, the toughening agent is specifically chlorinated polyethylene, and the mesh size of the secondary aluminum ash is 600-700 mesh.

[0052] The production method comprises the following steps:

[0053] (1) stirring the components to form a raw material mixture;

[0054] (2) The raw material mixture is added into a twin-screw extruder for extrusion. The temperature of each zone of the twin-screw extruder is: Ⅰ (conveying section) 200°C, Ⅱ (melting section) 190°C, Ⅲ (metering section) 180°C, and Ⅳ (die head) 185°C.

[0055] (3) The extruded melt is pressed and formed by a calender, and then peeled and cooled to room temperature to obtain a PVC sheet.

[0056] In this embodiment, the chemical composition (dry basis) of the secondary aluminum ash is as follows (mass percentage):

[0057] Element <![CDATA[Al2O3]]> MgO <![CDATA[SiO2]]> <![CDATA[Fe2O3]]> Cl <![CDATA[Na2O]]> CaO F AlN other content 61.92 3.86 8.54 3.46 3.15 2.34 2.54 2.54 10.13 1.52

[0058] Example 3

[0059] Preparation of 3# ceramic paraffin lubricant:

[0060] (1.1) The secondary aluminum ash, silicon dioxide, kaolin, montmorillonite and binder are mixed with a high-speed mixer, granulated, dried and calcined to obtain a granular ceramic sintered body; the binder is specifically bentonite. The mass ratio of secondary aluminum ash, silicon dioxide, kaolin, montmorillonite and binder is 70:15:4:6:5. The drying temperature is 130°C, the drying time is 3h, and the calcination process is as follows:

[0061] First, heat the temperature to 650°C at a rate of 12°C / min, then slowly heat the temperature to 980°C at a rate of 6°C / min, keep it at that temperature for 1 hour, then cool to room temperature, and then heat the temperature to 1300°C at a rate of 12°C / min, and keep it at that temperature for 3 hours.

[0062] (1.2) The granular ceramic sintered body is crushed and ground by a vertical mill and sieved by a 450-mesh screen, and the material under the sieve is taken as 3# ceramic powder. The porosity of 3# ceramic powder is 52%.

[0063] (1.3) The 3# ceramic powder is divided into two parts, namely the first ceramic powder and the second ceramic powder, and the volume ratio of the first ceramic powder to the second ceramic powder is 30:70. Under the vacuum condition of 70Pa absolute pressure, the paraffin is heated at 73°C to a molten state, and the first ceramic powder is immersed in the paraffin melt to make the paraffin penetrate into the micropores of the first ceramic powder. The vacuum is canceled, and the second ceramic powder is added to the paraffin, and stirred evenly to form a 3# ceramic paraffin lubricant. The volume ratio of the 3# ceramic powder to the paraffin is 1:1.5.

[0064] For the production of PVC sheets, the raw material formula includes the following components in parts by weight: 100 parts of PVC resin powder, 3 parts of heat stabilizer, 4 parts of processing aid, 2 parts of 3# ceramic paraffin lubricant, 1.2 parts of stearic acid, 4 parts of toughening agent, 65 parts of heavy calcium carbonate, and 45 parts of secondary aluminum ash; the heat stabilizer is specifically calcium stearate, the processing aid is specifically acrylic acid ester copolymer, the toughening agent is specifically chlorinated polyethylene, and the mesh size of the secondary aluminum ash is 700-800 mesh.

[0065] The production method comprises the following steps:

[0066] (1) stirring the components to form a raw material mixture;

[0067] (2) The raw material mixture is added into a twin-screw extruder for extrusion. The temperature of each zone of the twin-screw extruder is: Ⅰ (conveying section) 205℃ Ⅱ (melting section) 195℃ Ⅲ (metering section) 185℃ Ⅳ (die head) 190℃.

[0068] (3) The extruded melt is pressed and formed by a calender, and then peeled and cooled to room temperature to obtain a PVC sheet.

[0069] In this embodiment, the chemical composition (dry basis) of the secondary aluminum ash is as follows (mass percentage):

[0070] Element <![CDATA[Al2O3]]> MgO <![CDATA[SiO2]]> <![CDATA[Fe2O3]]> Cl <![CDATA[Na2O]]> CaO F AlN other content 70.56 1.65 7.44 1.63 2.48 2.41 1.59 2.34 7.12 2.78

[0071] By adopting the processes in the above embodiments, when producing PVC sheets, condensed paraffin wax will appear at the outlet of the shaping mold only after 26-28 days of normal continuous production.

[0072] Comparative Example 1

[0073] The comparative example 1 is substantially the same as the example 1, except that paraffin is directly used as a raw material component without adding ceramic powder.

[0074] The samples of each embodiment and comparative example were subjected to comparative performance tests:

[0075] Weigh 2.000g of the PVC sheet sample prepared in each embodiment, cut the PVC sheet sample into 5mm×5mm sheets, soak it in 23℃ gasoline at room temperature for 120 hours, take out the sample, filter the soaking liquid with a filter membrane, and use liquid chromatography to calculate the paraffin extraction rate in each sample. The paraffin extraction rates of Example 1, Example 2, Example 3 and Comparative Example 1 are 3.4%, 3.5%, 3.8% and 13.2% respectively. After replacing paraffin with ceramic paraffin lubricant, the paraffin extraction rate in the PVC sheet sample is reduced by 71-74%.

[0076] The paraffin extraction rate is A / B, where A is the weight content of paraffin in gasoline and B is the weight content of paraffin in the PVC sheet sample.

Claims

1. A ceramic paraffin lubricant for PVC sheets, characterized in that: The preparation method thereof comprises the following steps: (1.1) secondary aluminum ash, silicon dioxide, kaolin, montmorillonite and a binder are mixed, granulated, dried and calcined to obtain a granular ceramic sintered body; the binder is at least one of bentonite, tetraethyl orthosilicate and polyvinyl alcohol; (1.2) crushing and grinding the granular ceramic sintered body to obtain ceramic powder; (1.3) The ceramic powder is divided into two parts, namely a first ceramic powder and a second ceramic powder; under vacuum conditions, paraffin is heated at 60-80°C to a molten state, and the first ceramic powder is immersed in the paraffin melt to allow the paraffin to penetrate into the micropores of the ceramic powder. The vacuum is canceled, and the second ceramic powder is added to the paraffin, and stirred evenly to form a ceramic paraffin lubricant.

2. The ceramic paraffin lubricant according to claim 1, characterized in that In step (1.1), the mass ratio of secondary aluminum ash, silica, kaolin, montmorillonite and binder is (70-80):(10-15):(1-5):(3-8):(1-5).

3. The ceramic paraffin lubricant according to claim 1, characterized in that: In step (1.1), the roasting process is as follows: First, increase the temperature to 600-650℃ at a rate of 8-12℃ / min, then increase the temperature to 900-1000℃ at a rate of 3-6℃ / min, keep warm for 1-2h, then cool to room temperature, and then increase the temperature to 1300-1350℃ at a rate of 8-12℃ / min, and keep warm for 1-3h.

4. The ceramic paraffin lubricant according to claim 1, characterized in that: In step (1.2), the granular ceramic sintered body is crushed and ground, and then sieved with a 400-500 mesh sieve, and the sieved material is taken as ceramic powder.

5. The ceramic paraffin lubricant according to claim 1, characterized in that: In step (1.3), the vacuum degree is 20-100 Pa absolute pressure.

6. The ceramic paraffin lubricant according to claim 1, characterized in that: In step (1.3), the volume ratio of ceramic powder to paraffin is 1:(1.5-2.5).

7. The ceramic paraffin lubricant according to claim 1, characterized in that: The volume ratio of the first ceramic powder to the second ceramic powder is (20-30):(70-80).

Citation Information

Patent Citations

  • Porous ceramic material with adsorption and ion dissolution functions and manufacturing method thereof

    CN112408963A

  • Aluminum nitride composite ceramic and preparation method thereof

    CN117105673A

  • Lubricant vacuum impregnated in porous body consisting of sintered metal

    JP2017014473A